2016
DOI: 10.1055/s-0042-107793
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Seasonal Differences in Basal Metabolic Rate in Humans: A Cross-Sectional Study

Abstract: Some studies indicate that basal metabolic rate is greater winter than the summer, suggesting a role for brown fat in human thermogenesis. We examined whether there are clinically meaningful differences in basal metabolic rate under thermoneutral conditions between winter and summer months in inhabitants of Rochester, Minnesota. We collated data from 220 research volunteers studied in the winter (December 1 – February 28) and 214 volunteers studied in the summer (June 1 – August 31), 1995–2012. Basal metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Furthermore, the RMR measurement period (time of year) was not recorded since variations in metabolic rate due to seasonal variations have not been reported in many studies, regarding people who live in a modern western environment and are not exposed to a cold climate. Finally, the absence of the thermogenic effect of brown adipose tissue during seasonal variations has yet not been reported and needs further investigation [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the RMR measurement period (time of year) was not recorded since variations in metabolic rate due to seasonal variations have not been reported in many studies, regarding people who live in a modern western environment and are not exposed to a cold climate. Finally, the absence of the thermogenic effect of brown adipose tissue during seasonal variations has yet not been reported and needs further investigation [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The food was maximally saturated with vitamin A in spring, vitamin C in summer and autumn, and vitamin E in summer [64]. Several studies included in our meta-analysis reported no difference in caloric intake between winter and summer [42,43,53,54]. There were also no differences between men and women in the seasonal dynamics of the amount of calories consumed [43,53].…”
Section: Resultsmentioning
confidence: 73%
“…Kanikowska et al [38] observed a slight increase in leptin in winter in healthy young men. There are reports of an increase in cholesterol levels in winter without a significant change in triglyceride levels [38][39][40][41][42]. According to the results of some studies, the glucose level did not change during the year [41], according to the results of others, it was higher in winter than in summer [40].…”
mentioning
confidence: 94%
“…This may have influenced the REE, as the climate is one of the factors that influences its variability. In fact, some studies have already shown a higher REE in winter than in summer [50,51]. However, to minimize these effects we standardized the temperature and humidity of the environment where IC was performed so as to mitigate any seasonal influence on REE.…”
Section: Discussionmentioning
confidence: 99%